PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA MATERI BANGUN RUANG SISI LENGKUNG KELAS IX SMPN 3 TONDANO - Momongan, Jeremia; Mangobi, James U. L.; Ermita, Ermita (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to identify whether the learning outcomes of students who learn using the Problem Based Learning (PBL) model are higher than the learning outcomes of students who learn using the Conventional learning model on the material of Curved Side Spaces. This study used a posttest-only control group design. The population in this study were all grade IX students, with a sample consisting of grade IX A as an experimental class of 23 students and grade IX B as a control class of 23 students at SMP N 3 Tondano in the 2024/2025 school year. The results showed a difference in the learning outcomes of students taught with the Problem Based Learning (PBL) learning model compared to students taught with the Conventional learning model. Based on these results, it is concluded that learning using the Problem Based Learning (PBL) model can improve students' mathematics learning outcomes on the material of Curved Side Spaces.